Renal Protective Effects of Melatonin in Animal Models of Diabetes Mellitus-Related Kidney Damage: A Systematic Review and Meta-Analysis. (14th June 2022) - Luo, Qian; Cai, Yuzi; Zhao, Qihan; Jiang, Yuhua; Tian, Lei; Liu, Yuning; Liu, Wei Jing
Abstract : Diabetic nephropathy (DN)—chronic kidney damage caused by hyperglycemia—eventually develops into end-stage renal disease (ESRD). Melatonin is a powerful antioxidant that has a wide range of biological activities. Potentially helpful effects of melatonin on diabetic kidney disease have been found in several studies. However, its protective mechanisms are not clear and remain to be explored. In this review (CRD42021285429 ), we conducted a meta-analysis to estimate the effects and relevant mechanisms of melatonin for diminishing renal injuries in diabetes mellitus models. The Cochrane Library, PubMed, and EMBASE databases up to September 2021 were used. Random- or fixed-effects models were used for calculating the standardized mean difference (SMD) or 90% confidence interval (CI). The risk of bias was estimated using the SYRCLE's RoB tool. Statistical analysis was conducted with RevMan. A total of 15 studies including 224 animals were included in the analysis. The experimental group showed a remarkable decrease in serum creatinine (P = 0.002 ), blood urea nitrogen (P = 0.02 ), and urinary albumin excretion rate (UAER) (P < 0.00001 ) compared with the control group, while the oxidative stress index improved. The experimental group also showed a remarkable increase in superoxide dismutase (P = 0.21 ), glutathione (P < 0.0001 ), and catalase (P = 0.04 ) and a remarkable decrease in MDA (P < 0.00001 ) content compared with the control group. We concluded that melatonin plays a role in renal protection in diabetic animals by inhibiting oxidative stress. Moreover, it should be noted that fasting blood glucose was reduced in the experimental group compared with the control group. The kidney and body weights of the animals were not decreased in the diabetic animal model compared with the control group.